Effects of Drying Strategies and Microfibrillated Cellulose Fiber Content on the Properties of Foam-Formed Paper. (3rd July 2016) - Korehei, Reza; Jahangiri, Pouyan; Nikbakht, Abbas; Martinez, Mark; Olson, James
Abstract : A novel methodology was used to create a highly porous foam-formed paper that is bonded with highly refined cellulose fiber. In this process, cellulose pulp suspension at various consistencies (0.5, 1.0, 1.5, and 2%) was dispersed in water, followed by foam formation under high shear forces in the presence of a surfactant. Various drying methods were used to achieve foam formation. These included freeze-drying (FD), vacuum-dewatered air-drying (VAD), and dewatered freeze-drying (VFD). Increasing the pulp's consistency and changing the drying techniques from freeze-drying to air-drying resulted in a more compact morphological structure and increased density of foam-formed paper samples. Densification of foam-formed samples was measured using a Dynamic Mechanical Analysis (DMA) machine and a sample with densification at lowest strain value was obtained by a 10 wt% addition of microfibrillated cellulose fiber (MFC). At 10 wt% MFC addition, denser foam-formed paper samples with enhanced microstructure were obtained. Air filtration efficiency and acoustic properties of foam-formed paper were also characterized and optimized by the addition of MFC.